Difference between uric acid stones and non-uric acid stones in conventional CT scanning - LIU Huan, YANG Xue-dong, SHI Feng-xiang, WU Zhe, SUN Hao, JIN Zheng-yu (Jichu yixue yu linchuang, 2021)
Objective To investigate methods for predicting uric acid stones with conventional CT by measuring the CT value of stones, mean diameter size, density of stones, stone to kidney CT value ratio, and body width. Methods Patients underwent conventional CT scanning and were diagnosed postoperatively before uric acid stones and non-uric acid stones were detected by dual-energy CT.A total of 50 patients with uric acid stones and 60 patients with non-uric acid stones were enrolled, and after stones were detected by conventional CT scan, uric acid stones and non-uric acid stones were distinguished by dual-energy CT. The selected stones were ＞ 7 mm in long diameter. Data acquisition was performed on enrolled patients by a radiologist blinded to stone composition. The predictive value of each index was evaluated by independent sample t test, chi-square test, and receiver operating characteristic curve (ROC). Results There was great value in distinguishing uric acid stones from non-uric acid stones in stone CT value (P＜0.01), significant statistical difference in uniform stones or not and in size (P＜ 0.05). The CT scan showed a high predictive value for the diagnosis of uric acid stones, with AUC=0.948, sensitivity as 94%,and specificity as 85%.According to the ROC curve, the CT scaning value of 730 HU was adopted as the threshold for the diagnosis of uric acid stones, with a positive predictive value of 83.9%, a negative predictive value of 94.4%, and an accuracy of 80.1%. The size of the stone also had a predictive value, AUC=0.63, sensitivity 36%, and specificity 88.3%, and the mean diameter of the stone greater than 18.05 mm was defined as a diagnosis standard of uric acid stones according to the ROC curve, which had a positive predictive value of 72%, a negative predictive value of 62.4%, and an accuracy of 64.5%. Using a stone CT value of 730 HU as the threshold combined with a uniform stone density to predict uric acid stones, its specificity was 100% and the positive predictive value was 100%. Conclusions Conventional CT is of high value in differentiating uric acid calculi from non-uric acid calculi by measuring the mean diameter size and density of calculi. When evaluate CT result with or without homogenous stone density as the diagnostic criteria, the specificity and positive predictive value of diagnosing uric acid calculi are significantly higher.